( - 0,1) do potęgi 3 + ( -2,3) do potęgi 2 =
wykonaj działania
a) 3 do potęgi 3 - ( - 2) do potegi 4 =
b) -4 do potęgi 2 - ( -10) do potęgi 0 =
c) -[ - ( -5) do potęgi 2 + ( -1) do potęgi 3]=
d) ( -6) do potęgi 3 + (-3) do potęgi 6=
e) -5 do potęgi 2 + 2 do potęgi 5=
f) -[-(-4) do potegi 3 - 3 do potegi 4 ]=
g) -(-8) do potęgi 2 -[ - ( -3) do potęgi 2 ] do potęgi 3=
h) - 125 do potęgi 0 - ( -5) do potęgi 3 =
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
- 0,1) do potęgi 3 + ( -2,3) do potęgi 2 =-0,001+5,29=5,289
wykonaj działania
a) 3 do potęgi 3 - ( - 2) do potegi 4 = 27-16=11
b) -4 do potęgi 2 - ( -10) do potęgi 0 =16-1=15
c) -[ - ( -5) do potęgi 2 + ( -1) do potęgi 3]=-[-25-1]=-(-26)=26
d) ( -6) do potęgi 3 + (-3) do potęgi 6=-216+729=513
e) -5 do potęgi 2 + 2 do potęgi 5=25+32=57
f) -[-(-4) do potegi 3 - 3 do potegi 4 ]=-[64-81]=-[-17]=17
g) -(-8) do potęgi 2 -[ - ( -3) do potęgi 2 ] do potęgi 3=-64-[-9]^3=-64+729=665
h) - 125 do potęgi 0 - ( -5) do potęgi 3 =1-(-125)=1+125=126
( - 0,1) do potęgi 3 + ( -2,3) do potęgi 2 = -0,001 + 5,29 = 5,289
3 do potęgi 3 - ( - 2) do potegi 4 = 27 - 16 = 11
-4 do potęgi 2 - ( -10) do potęgi 0 = 16 - 1 = 15
-[ - ( -5) do potęgi 2 + ( -1) do potęgi 3]= -[-25+(-1)] = - (-26) = 26
( -6) do potęgi 3 + (-3) do potęgi 6= -216 + 729 = 513
-5 do potęgi 2 + 2 do potęgi 5= 25 + 32 = 57
-[-(-4) do potegi 3 - 3 do potegi 4 ] = -[-(-64)-81] = -(64-81) = -(-17) = 17
-(-8) do potęgi 2 -[ - ( -3) do potęgi 2 ] do potęgi 3= - 64 - (- 9)^3 = -64 - (-729) = 665
- 125 do potęgi 0 - ( -5) do potęgi 3 = 1 - (-125) = 126